The effects of hydrogen addition on the chemical kinetics of hydrogen-hydrocarbon flames: A computational study - Zine labidine Messaoudani; Mahar Diana Hamid; Che Rosmani Che Hassan; Yajue WU (South African Journal of Chemical Engineering, 2020)
In this paper, the effects of hydrogen addition on the chemical kinetics of hydrogen–hydrocarbon flames were investigated numerically. Profiles of maximum OH, O and H radical mole fractions, flame temperature and emission levels of hydrogen-methane, hydrogen-ethane and hydrogen-propane flames were computational obtained using Kintecus solver code. The simulations were performed by incorporating Konnov's hydrocarbon combustion mechanism at the stoichiometric condition and the constant pressure of 1 atm. It was found that a small hydrogen increase in the flame mixture can modestly affects the temperature and mole fraction profiles, however, the significant increase can be observed upon 40%, 60% and 80% of hydrogen addition for hydrogen-methane, hydrogen-ethane and hydrogen-propane flames respectively can lead to decrement of CO and CO2 emissions but increment in the combustion kinetics and the adiabatic flame temperature plus an extension of the flame stability limits. A comparison of the flames free radical profiles and the laminar burning velocity of the flames showed a strong correlation.